Emergence of dynamical order : synchronization phenomena in complex systems - 364047 Manrubia, Susanna C.; Mikhailov, A. S. (Alexander S.), 1950-; Zannette, Damian H. (River Edge, N.J. : World Scientific, 2004)
41